2021
DOI: 10.1111/jocd.14641
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of teledermatological examinations with conventional office visits in management of acne vulgaris: A review of current literature

Abstract: Acne vulgaris is the most common skin disease in the world, particularly affecting adolescents and young adults. Telemedicine has grown rapidly in the past few years and represents a new simplification in modern medicine. The aim of this literature review is to provide an overview of acne vulgaris in teledermatology and to identify the differences between teledermatological examinations and face‐to‐face consultations. For this purpose, a systematic literature search of the PubMed database was performed, up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Young people are nowadays on average more engaged with technology and the internet than previous generations ( 5 ). This familiarity can positively influence the satisfaction of adolescent patients with teledermatology, since for most of these patients the correct handling of smartphones and telemedicine programs does not involve a big learning effort ( 5 , 8 ). Furthermore, such teledermatological check-ups might save patients’ time and avoid absences either at school or at work ( 5 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Young people are nowadays on average more engaged with technology and the internet than previous generations ( 5 ). This familiarity can positively influence the satisfaction of adolescent patients with teledermatology, since for most of these patients the correct handling of smartphones and telemedicine programs does not involve a big learning effort ( 5 , 8 ). Furthermore, such teledermatological check-ups might save patients’ time and avoid absences either at school or at work ( 5 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that acne vulgaris affects up to 85% of subjects between 12 and 24 years old ( 3 , 4 ) showing significant potential for using new treatment concepts such as telemedicine. Telemedicine transfers the doctor’s consultation into a virtual space ( 5 ). This is done by transmitting pre-prepared questionnaires that the patient has to fill in or by direct communication via video consultation ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, acne and hemangiomas may be amenable to telehealth as they often affect localized areas and can be easily visualized using patientsubmitted photographs. 1,2 Contact dermatitis may be diagnosed virtually given it is often geometric and localized especially in combination with a carefully-obtained confirmatory history of localized cutaneous exposure to an allergen or irritant. 3 In contrast, atopic dermatitis may require in-person evaluation, as it may present diffusely on the body and exhibit texture changes that are difficult to appreciate without direct examination.…”
mentioning
confidence: 99%